Literary Bioethics : Animality, Disability, and the Human - Linett, Maren Tova; Linett, Maren Tova (Book collections on Project MUSE., 2020)
Uses literature to understand and remake our ethics regarding nonhuman animals, old human beings, disabled human beings, and cloned posthumansLiterary Bioethics argues for literature as an untapped and essential site for the exploration of bioethics. Novels, Maren Tova Linett argues, present vividly imagined worlds in which certain values hold sway, casting new light onto those values; and the more plausible and well rendered readers find these imagined worlds, the more thoroughly we can evaluate the justice of those values. In an innovative set of readings, Linett thinks through the ethics of animal experimentation in H.G. Wells's The Island of Doctor Moreau, explores the elimination of aging in Aldous Huxley's Brave New World, considers the valuation of disabled lives in Flannery O'Connor's The Violent Bear It Away, and questions the principles of humane farming through reading Kazuo Ishiguro's Never Let Me Go, where cloned human beings are used systematically by the government as organ donors. By analyzing novels published at widely spaced intervals over the span of a century, Linett offers snapshots of how we confront questions of value.In some cases the fictions are swayed by dominant devaluations of nonnormative or nonhuman lives, while in other cases they confirm the value of such lives by resisting instrumental views of their worth--views that influence, explicitly or implicitly, many contemporary bioethical discussions, especially about the value of disabled and nonhuman lives. Literary Bioethics grapples with the most fundamental questions of how we value different kinds of lives, and questions what those in power ought to be permitted to do with those lives as we gain unprecedented levels of technological prowess.